Physical and Psychological Violence in Dating Adolescents: Who are the Victims? - Ahmad Ahid Mudayana; Erni Gustina; Yuniar Wardani; Suci Musvita Ayu; Liena Sofiana; Moh Irma Sukarelawan (Universitas Aisyah Pringsewu, 2023)
Background: Dating violence is experienced by many adolescents. It's just that it is considered normal because of commitment in dating relationships. This study examines forms of dating violence, intending to get an overview of the most dominant forms of dating violence experienced by males and females. Method: The type of research used is quantitative research with a cross-sectional approach. The research sample consisted of 313 adolescents aged 18-24 years who had or were in a dating relationship and had or were experiencing violence during a dating relationship. Researchers collected primary data using courtship violence instruments. Results: The dominant frequency of victims experiencing physical and psychological violence was in the frequent category, namely 31.0% (26.8% female and 4.2% male). Meanwhile, in the very frequent category, the number of victims experiencing physical and psychological violence was 17% (15.4% female and 1.6% male). The type of violence experienced by adolescents was psychological violence in the very high category of 40% (underestimating, demanding, getting angry when reprimanded, limiting associations, limiting male friends, not respecting feelings, bringing up the past, and saying hurtful things). The high category was experienced for psychological violence, as much as 22.5% (underestimated partner, scolded partner, stingy, treated like a fool, rude, ridiculed appearance, threatened, shouted and shouted at partner, and scared), while physical violence was 7.5% (pushing, pulling and demanding to do something you want). Conclusion: Dating violence can be experienced by both males and females. The frequency of males experiencing dating violence is smaller than that of females. Males are more dominant in experiencing physical violence, while females are more dominant in experiencing psychological violence.Abstrak: Latar Belakang: Kekerasan dalam pacaran banyak dialami oleh remaja. Hanya saja dianggap biasa saja karena komitmen dalam hubungan pacaran. Penelitian ini mengkaji bentuk-bentuk kekerasan dalam pacaran, bermaksud untuk mendapatkan gambaran tentang bentuk-bentuk kekerasan dalam pacaran yang paling dominan dialami oleh laki-laki dan perempuan. Metode: Jenis penelitian yang digunakan adalah penelitian kuantitatif dengan pendekatan cross sectional. Sampel penelitian terdiri dari 313 remaja berusia 18-24 tahun yang pernah atau sedang menjalin hubungan pacaran dan pernah atau sedang mengalami kekerasan saat berpacaran. Peneliti mengumpulkan data primer dengan menggunakan instrumen kekerasan pacaran. Hasil: Frekuensi dominan korban mengalami kekerasan fisik dan psikis termasuk kategori sering yaitu 31,0% (26,8% perempuan dan 4,2% laki-laki). Sedangkan pada kategori sangat sering, jumlah korban yang mengalami kekerasan fisik dan psikis sebanyak 17% (15,4% perempuan dan 1,6% laki-laki). Jenis kekerasan yang dialami remaja adalah kekerasan psikis dengan kategori sangat tinggi yaitu 40% (meremehkan, menuntut, marah jika ditegur, membatasi pergaulan, membatasi teman laki-laki, tidak menghargai perasaan, mengungkit masa lalu, dan mengatakan hal-hal yang menyakitkan). Kategori tinggi dialami untuk kekerasan psikis, sebanyak 22,5% (diremehkan pasangan, dimarahi pasangan, pelit, diperlakukan seperti orang bodoh, kasar, penampilan diejek, diancam, dibentak dan dibentak pasangan, dan ketakutan), sedangkan kekerasan fisik sebesar 7,5%. % (mendorong, menarik dan menuntut untuk melakukan sesuatu yang Anda inginkan). Kesimpulan: Kekerasan dalam pacaran dapat dialami baik oleh laki-laki maupun perempuan. Frekuensi laki-laki yang mengalami kekerasan dalam pacaran lebih kecil dibandingkan perempuan. Laki-laki lebih dominan mengalami kekerasan fisik, sedangkan perempuan lebih dominan mengalami kekerasan psikis.